USE OF ALLEGRO WEBSITE IN E-BUSINESS ADDRESSED TO FARMERS - Sieczko, Anna; Sieczko, Leszek (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article estimates the volume of products supply and shows the regional variation of e-commerce addressed to farmers by Allegro.pl auction portal. In order to determine the multi-characteristic similarity between regions of Poland, a multi-dimensional cluster analysis was conducted, grouping the regions according to the amount and the value of products listed in various subcategories. Products in the various subcategories showed significant diversity, depending on the region and regarding assortment’s value and its individual variety as well.